Analisis Tindakan Sosial Pada Penerapan Personal Hygiene Cook Di Kitchen The Royal Santrian Luxury Beach Villas - Rejeki, Winda Sephia; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2024)
In the tourism industry, it is necessary to demonstrate comfort, quality, and gastronomy. Aside from that, however, the comfort and assurances that align with the objectives of the individuals using these facilities are crucial. Employees in the hotel sector of the tourism industry are subject to numerous rules and regulations, one of which is to always pay attention to personal hygiene. Every employee makes a personal hygiene effort to preserve their own well-being, appearance, and surroundings. This is crucial because every worker will represent the hotel's caliber. Using Max Weber's Social Action Theory, this study intends to examine how chefs at The Royal Santrian Luxury Beach Villas apply personal cleanliness. This study employs a qualitative approach using a descriptive approach. The data collected will be analyzed based on the researcher's ability to reason through the presentation of observations and the analysis of problems found in the field. The research's conclusions are based on social behaviors using Max Weber's theoretical framework, which serves as the primary source of information on the many reasons and objectives behind chefs' use of personal hygiene. The study's conclusion is that Max Weber used a social strategy and technique to examine how chefs apply personal cleanliness, the idea of cooking, and the acts and customs that are crucial to the habitual process. Keywords: Social Action, Personal Hygiene, Cook, Kitchen